High spin structure of 155Dy - Papadopoulos, C. T.; Vlastou, R.; Serris, M.; Kalfas, C. A.; Fotiades, N.; Harissopulos, S.; Kosslonides, S.; Rilley, M. A.; Simpson, J.; Paul, E. S.; Sharpey-Schafer, J. F. (HNPS Advances in Nuclear Physics, 2019)
High spin states in 155Dy have been studied by γ-γ coincidence measurements via the 124Sn(36S, 5n)155Dy reaction at a beam energy of 155 MeV. Eight rotational bands have been populated and observed up to high spin (I<91/2).The band features have been analysed within the framework of the cranked shell model. The Ì13/2 neutron alignments and the h11/2 proton alignments are discussed. B(M1)/B(E2) ratios have also been extracted for the strongly coupled bands to deduce further information on the detailed structure of these bands. For the highest states (above spin 30) of the negative parity bands an irregularity in y-ray energies appears which is discussed in terms of band termination.